PENGARUH FINANCIAL BEHAVIOR TERHADAP KEPUTUSAN INVESTASI PADA CIVITAS ACADEMICA UNIVERSITAS LOGISTIK DAN BISNIS INTERNATIONAL BANDUNG - Nasrudin, Nasrudin (Universitas Logistik dan Bisnis Internasional, 2025)
This study aims to examine the influence of financial behavior on investment decisions among students, lecturers, and staff at the Universitas Logistik dan Bisnis Internasional. The research method employed is a survey with a quantitative approach. Data were collected through questionnaires distributed to 88 respondents who are actively investing. Data analysis was conducted using linear regression to test the relationship between the independent variable (financial behavior) and the dependent variable (investment decision). The study emphasizes the importance of financial literacy and sound financial behavior in making investment decisions. Individuals with good financial habits tend to make wiser and more balanced investment decisions. Therefore, financial education that focuses on improving financial behavior can contribute to better investment decisions and enhance individual financial well-being.